ANALYTICAL STUDY ON INCENTIVE TRAVEL AND MOTIVATION - Ms. Devika Sood, Dr.M. Sajnani ,Dr. Prashant Kumar Gautam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The part of incentive travel is talked about and the capability of the Indian generated incentive travel market is inspected. In view of the information gathered, proposals for additional business advancement were given to DMC. Travel motivation hypothesis assists with clarifying which specific parts of travel make it an appealing prize. The article presents an early on applied structure for understanding the connection between motivator travel and work inspirations and goes about as an establishment for future examination here. The outcomes gave significant ramifications to Indian travel organizations and policy creators, and worldwide incentive travel clients and organizers to see better the condition of incentive travel opportunities in India.